How Low Can You Go: Methane Production of Methanobacterium congolense at Low CO2 Concentrations - Chen, Xihan; Ottosen, Lars Ditlev Mørck; Kofoed, Michael Vedel Wegener (Frontiers in Bioengineering and Biotechnology, 2019)
Autotrophic hydrogenotrophic methanogens use H2/CO2 as sole carbon and energy source. In contrast to H2, CO2 is present in high concentrations in environments dominated by methanogens e.g., anaerobic digesters (AD), and is therefore rarely considered to be a limiting factor. Nonetheless, potential CO2 limitation can be relevant in the process of biomethanation, a power-to-gas technology, where biogas is upgraded by the addition of H2 and ideally reduce the CO2 concentration in the produced biogas to 0–6%. H2 is effectively utilized by methanogens even at very low concentrations, but little is known about the impact of low CO2 concentrations on methanogenic activity. In this study, CO2 consumption and CH4 production kinetics under low CO2 concentrations were studied, using a hydrogenotrophic methanogen, Methanobacterium congolense, as model organism. We found that both cellular growth and methane production were limited at low CO2 concentrations (here expressed as Dissolved Inorganic Carbon, DIC). Maximum rates (Vmax) were reached at [DIC] of 100 mM (extrapolated), with a CO2 consumption rate of 69.2 fmol cell−1 d−1 and a CH4 production rate of 48.8 fmol cell−1 d−1. In our experimental setup, 80% of Vmax was achieved at [DIC] >9 mM. DIC half-saturation concentrations (Km) was about 2.5 mM for CO2 consumption and 2.2 mM for CH4 production. No CH4 production could be detected below 44.4 μM [DIC]. These data revealed that the limiting concentration of DIC may be much higher than that of H2 for a hydrogenotrophic methanogen. However, DIC is not a limiting factor in ADs running under standard operating conditions. For biomethanation, the results are applicable for both in situ and ex situ biomethanation reactors and show that biogas can be upgraded to concentrations of 2% CO2 (98% CH4) while still retaining 80% Vmax at pH 7.5 evaluated from M. congolense. Since DIC concentration can vary significantly with pH and pCO2 during biomethanation, monitoring DIC concentration through pH and pCO2 is therefore important for keeping optimal operational conditions for the biomethanation process.